2012
DOI: 10.1111/j.1399-5448.2012.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of type 1 diabetes in Republic of Srpska (Bosnia and Herzegovina) and Slovenia in the period 1998-2010

Abstract: The incidence for age group 0-18 yr standardized to the world population is remarkably higher in Slovenia than in the Republic of Srpska. Further follow-up and investigations are needed to explain the high difference in incidence of T1DM between the two geographically related countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Our results are similar for both genders. This is in accordance with the latest findings from Germany, the Netherlands and Slovenia, although the results of other studies are inconclusive [17,[24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are similar for both genders. This is in accordance with the latest findings from Germany, the Netherlands and Slovenia, although the results of other studies are inconclusive [17,[24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 92%
“…The standardized incidence of T1DM for the 0-14 years age group in the Republika Srpska (a self-governing entity in Bosnia and Herzegovina) was estimated to be 8.2 cases /100 000 and the annual increase in the incidence was estimated to be 2.3% for the 1998-2010 period (5). These results allow the conclusion that the Republika Srpska may be placed within the group of European regions with a low incidence of T1DM.…”
Section: Introductionsupporting
confidence: 51%
“…The youngest age group was once believed to have the fastest growth in T1D incidence . Recently, however, quite a few studies reporting 5 to 9 years or 10 to 14 years as the age group with the greatest annual increase seem to have conflicted with the mainstream finding that the youngest age group, 0 to 4 years, exhibits the most substantial increase in T1D incidences . Although most epidemiological investigations focus on the age group of 0 to 14 years and data of patients with T1D aged over 14 years are insufficient, studies conducted in the United Kingdom, Mexico, Israel, and the United States have revealed a significant increment in T1D incidences for youth aged 15 to 34, 15 to 19, 15 to 17, and 15 to 19 years respectively.…”
Section: Epidemiologymentioning
confidence: 99%
“…9,31,42 In contrast to the consistently high incidence rates in Caucasians, incidences of T1D in Arabs range from as high as 40.9/100 000 in Kuwait 27 to 29.0/100 000 in Saudi Arabia 3 to slightly higher than 10/100 000 in Israel. 18 Next come countries in southeast Europe 12,35,[37][38][39] which usually manifest a moderate risk for T1D with incidences around 10/ 100 000 person-years. Last, but not least, incidences as low as 1 to 5 cases/100 000 person-years are not uncommon in Latin America, 40,43 Africa, 19,41 and Asia.…”
Section: Incidence Of T1dmentioning
confidence: 99%